2017
DOI: 10.5114/biolsport.2017.65997
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, heart rate and perceived enjoyment after small-sided soccer games and repeated sprint in untrained healthy adolescents

Abstract: The purpose of this study was to examine systolic (SBP) and diastolic blood pressure (DBP), heart rate (HR), rating of perceived exertion (RPE) and perceived enjoyment responses to a repeated-sprint training session (RST) compared to a small-sided soccer game session (SSG) in untrained adolescents. Twelve healthy post-pubertal adolescent males (age 15.8±0.6 years, body mass 59.1±3.7 kg, height 1.7±0.1m) performed RST and SSG sessions in a randomized and counterbalanced order. Blood pressure and HR were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
(41 reference statements)
1
25
0
Order By: Relevance
“… 12 It has been reported that the positive effects of recreational soccer can be explained by the high exercise intensity achieved during training. 36 In the present study, the mean HR was 84.6% of HR peak , a value that is comparable to that obtained in adult participants, where HR generally exceeded 80% of HR max . 35 In addition to the high exercise intensity, recreational soccer represents an odd-impact physical activity that involves intense actions and movements in different directions.…”
Section: Discussionsupporting
confidence: 87%
“… 12 It has been reported that the positive effects of recreational soccer can be explained by the high exercise intensity achieved during training. 36 In the present study, the mean HR was 84.6% of HR peak , a value that is comparable to that obtained in adult participants, where HR generally exceeded 80% of HR max . 35 In addition to the high exercise intensity, recreational soccer represents an odd-impact physical activity that involves intense actions and movements in different directions.…”
Section: Discussionsupporting
confidence: 87%
“…19 Investigations that have utilized the PACES have evaluated enjoyment as a determinant of training sessions and related motivation. 11,21 To the knowledge of the authors, no previous study has directly compared physiological responses, muscular power and physical enjoyment of HIIT and SSGs in competitive soccer players. Given the importance of physical enjoyment in athlete motivation and the potential influences of exercise intensity, exertion and muscular fatigue, research to fill this gap in the literature is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other sports (e.g. endurance and strength training) shortterm SSSG resulted in high exercise intensities inducing neuromuscular and metabolic stress and perceptual responses [5,[7][8][9][10][11][12]. In fact, the average heart rates (HR) were around and even above 80%…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d m a n u s c r i p t of individual HR max and blood lactate concentrations exceeding 6 mmol/l [5,[7][8][9][10]12]. Several long term studies and reviews demonstrated that SSSG training may represent an effective strategy of multicomponent training that can induce greater positive effects on specific skills tasks when compared with interval or agility training and moderate to large improvements in team sport-related physical fitness [5,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation